Bioengineering toward direct production of immobilized enzymes: A paradigm shift in biocatalyst design. Issue 1 (1st January 2018) - Rehm, Fabian B. H.; Chen, Shuxiong; Rehm, Bernd H. A.
ABSTRACT: The need for cost-effectively produced and improved biocatalysts for industrial, pharmaceutical and environmental processes is steadily increasing. While enzyme properties themselves can be improved via protein engineering, immobilization by attachment to carrier materials remains a critical step for stabilization and process implementation. A new emerging immobilization approach, the in situ immobilization, enables simultaneous production of highly active enzymes and carrier materials using bioengineering/synthetic biology of microbial cells. In situ enzyme immobilization holds the promise of cost-effective production of highly functional immobilized biocatalysts for uses such as in bioremediation, drug synthesis, bioenergy and food processing.